2017
DOI: 10.1088/1361-648x/aa5140
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of transmission functions for an optimized three-terminal quantum dot heat engine

Abstract: We consider two modifications of a recently proposed three-terminal quantum dot heat engine. First, we investigate the necessity of the thermalization assumption, namely that electrons are always thermalized by inelastic processes when traveling across the cavity where the heat is supplied. Second, we analyze various arrangements of tunneling-coupled quantum dots in order to implement a transmission function that is superior to the Lorentzian transmission function of a single quantum dot. We show that the maxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Obviously the filtering properties are affected by the interactions which broaden or split the density of states rendering the filter less effective. This agrees with previous attempts at optimizing heat engines by engineering the transmission function [27,125]. On the other hand, strong interactions are responsible for the second leaf on the efficiency vs. power plane, visible in Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Obviously the filtering properties are affected by the interactions which broaden or split the density of states rendering the filter less effective. This agrees with previous attempts at optimizing heat engines by engineering the transmission function [27,125]. On the other hand, strong interactions are responsible for the second leaf on the efficiency vs. power plane, visible in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The main conclusion was that albeit the screening modifies the parameters at which the engine is optimal, it does neither change the maximal power nor the efficiency at the maximum power. A similar heat engine has also been optimized with respect to the transmission function [125].…”
Section: Three-terminal Heat Engine: the Role Of Strong Coulomb Inter...mentioning
confidence: 99%
“…In the former structure an almost rectangle window of transparency, described in 18 , is converted into an almost rectangle window of reflectivity (48) just by adding the same single-channel wire in parallel. Such rectangle windows of transmission can be applied 68 within the area of quantum heat engines. 69,70 Other fields of possible applications are broad band filters design 71 and 2D photonic crystals 72,73 formed by 2D periodic arrays of dielectric rods with an in-plane light wave, which is polarized along these rods.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission shape flattening was obtained by a special selection of hoping matrix elements in one dimensional chain representing a molecular conductor. A regular procedure of constructing quantum conductors with near rectangular transmission shape was presented in [133][134][135]. It was shown that such transmission shape results from resonance coalescence at the exceptional point of quantum conductor.…”
Section: Quantum Interferencementioning
confidence: 99%